A new fluorescent chemosensor for highly selective and sensitive detection of inorganic phosphate (Pi) in aqueous solution and living cells1. Issue 66 (19th July 2015) - Meng, Qingtao; Wang, Yue; Yang, Ming; Zhang, Run; Wang, Renjie; Zhang, Zhiqiang
<x xml:space="preserve">Abstract</x> A new fluorescein-based chemosensor, FP-Fe3+, was developed for the detection of inorganic phosphate (Pi) in aqueous solution and living cells.